1999
DOI: 10.1074/jbc.274.53.38177
|View full text |Cite
|
Sign up to set email alerts
|

The Retinal Rod Na+/Ca2+,K+Exchanger Contains a Noncleaved Signal Sequence Required for Translocation of the N Terminus

Abstract: The retinal rod Na ؉ /Ca 2؉ ,K ؉ exchanger (RodX) is a polytopic membrane protein found in photoreceptor outer segments where it is the principal extruder of Ca 2؉ ions during light adaptation. We have examined the role of the N-terminal 65 amino acids in targeting, translocation, and integration of the RodX using an in vitro translation/translocation system. cDNAs encoding human RodX and bovine RodX through the first transmembrane domain were correctly targeted and integrated into microsomal membranes; deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…SLC24A1 encodes a sodium/calcium, potassium exchanger (NCKX1) that removes intracellular calcium by exchanging four sodium ions for one calcium and one potassium [128]. The p.Leu26Phe substitution identified in MS patients is part of an uncleaved signal peptide sequence required for efficient membrane targeting and integration [129]. This signal sequence is highly conserved in mammals, including the p.Leu26 residue (Fig 4), but no homologous region exist in paralogs.…”
Section: Resultsmentioning
confidence: 99%
“…SLC24A1 encodes a sodium/calcium, potassium exchanger (NCKX1) that removes intracellular calcium by exchanging four sodium ions for one calcium and one potassium [128]. The p.Leu26Phe substitution identified in MS patients is part of an uncleaved signal peptide sequence required for efficient membrane targeting and integration [129]. This signal sequence is highly conserved in mammals, including the p.Leu26 residue (Fig 4), but no homologous region exist in paralogs.…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions, the corresponding region in the AChE translation product would become a transmembrane domain in an N-terminally extended (and 16% larger) AChE variant (hN-AChE). Analogous situations have been described for the asialoglycoprotein receptor (20), adrenal dopamine ␤-monooxygenase (22), ␣-neurexin (an extended form of ␤-neurexin) (23), retinal RodX exchanger (24), prion protein (25), and cyclooxygenase (26). COX-1, the classic cyclooxygenase form, includes a signal peptide at the N terminus.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, it was suggested that, like NCX1, bovine rod NCKX1 contained a cleavable N-terminal signal sequence, since N-terminal sequencing of the purified bovine rod NCKX1 led to a sequence starting at Asp66 (3). In contrast, analysis of bovine rod NCKX1 polypeptides obtained in a cell-free system showed no evidence for cleavage but suggested that the N-terminal sequence was important for a proper topology, inferred by glycosylation of the extracelluar loop (11).…”
mentioning
confidence: 99%